Non‐alcoholic fatty liver disease and sarcopenia additively increase mortality: a Korean nationwide survey. Issue 4 (2nd June 2021) - Moon, Joon Ho; Koo, Bo Kyung; Kim, Won
Abstract: Background: Sarcopenia is an independent risk factor not only for advanced‐stage non‐alcoholic fatty liver disease (NAFLD) but also for mortality. We investigated the association of sarcopenia and/or NAFLD with mortality among the Korean general population. Methods: Individuals aged 35–75 years without any history of cancer, ischaemic heart disease, ischaemic stroke, or secondary causes of chronic liver disease were selected from the Korean National Health and Nutrition Examination Surveys from 2008 to 2015. Their mortality data until December 2018 were retrieved from the National Death Registry. NAFLD and sarcopenia were defined by hepatic steatosis index and appendicular skeletal muscle mass divided by body mass index (BMI), respectively. Results: A total of 28 060 subjects were analysed [mean age, 50.6 (standard error, 0.1) years, 48.2 (0.3) % men]; the median follow‐up duration was of 6.8 (interquartile range, 4.8, 8.4) years. NAFLD predicted mortality after adjustment for age, sex, BMI, hypertension, dyslipidaemia, and smoking (HR 1.32, 95% CI 1.03–1.70), but this prediction lost its statistical significance after additional adjustment for diabetes mellitus. In contrast, NAFLD with advanced fibrosis independently increased the risk of mortality after adjustment for all covariates (HR 1.68, 95% CI 1.02–2.79). Stratified analysis revealed that NAFLD and sarcopenia additively increased the risk of mortality as an ordinal scale (HR 1.46, 95% CI 1.18–1.81, P for trend = 0.001). The coexistence of NAFLD and sarcopenia increased the risk of mortality by almost twice as much, even after adjustment for advanced fibrosis (HR 2.18, 95% CI 1.38–3.44). Conclusions: Concurrent NAFLD and sarcopenia conferred a two‐fold higher risk of mortality. The observation that NAFLD and sarcopenia additively increase mortality suggests that risk stratification would be helpful in predicting mortality among those with metabolic derangement.